MANGROVE FLORAL COMPOSITION AND ZONATION IN WESTERN LEYTE - Sebidos, R.F.; Galinato, M.I. (Annals of Tropical Research, 1996)
Mangroves are a community of trees or shrubs thriving along tidal flats and coastlines extending inland along rivers, streams and their tributaries with brackish waters. A floral composition survey identified 14 species of true mangrove trees belonging to 8 families, and 11 associated species in 10 families, present in 12 different towns of W. Leyte. Mangrove communities within and between sites markedly differ in their zoning pattern. In the northern part Sonneratia dominated the seaward edges while Avicennia in the landward fringes. However, in the southern part Rhizophora is found in the seaward edge while a mixture of Sonneratia, Ceriops and Avicennia occupied the landward zone.